Characteristics of melatonin-positive-labeled cells of gastric mucosa amount in rats of different sexes in autumn and winter = Характеристика кількості мелатонін-позитивно-мічених клітин слизової оболонки шлунка у щурів різної статі у осінньо-зимовий період = Характеристика количества мелатонин-положительно-меченых клеток слизистой оболочки желудка у крыс разного пола в осенне-зимний период - V. V. Hnatiuk (Kazimierz Wielki University, 2017)
Hnatiuk V. V. Characteristics of melatonin-positive-labeled cells of gastric mucosa amount in rats of different sexes in autumn and winter = Характеристика кількості мелатонін-позитивно-мічених клітин слизової оболонки шлунка у щурів різної статі у осінньо-зимовий період = Характеристика количества мелатонин-положительно-меченых клеток слизистой оболочки желудка у крыс разного пола в осенне-зимний период. Journal of Education, Health and Sport. 2016;6(11):622-628. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.200416 http://ojs.ukw.edu.pl/index.php/johs/article/view/4064         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016.   UDC 612.325: 612.6.057: 616.831.45   CHARACTERISTICS OF MELATONIN-POSITIVE-LABELED CELLS OF GASTRIC MUCOSA AMOUNT IN RATS OF DIFFERENT SEXES IN AUTUMN AND WINTER   V. V. Hnatiuk   National University of Pharmacy, Kharkiv, Ukraine gvalery_nice@ukr.net   Abstract The objective of presented study was the state of the melatonin-positive-labeled cells of gastric mucosa in rats of different sex and age in the autumn and winter. It was established that during the seasonal physiological desynchronosis -  autumn - the amount of melatonin-positive-labeled cells was lower compared to their level in the winter to 13 % - in male rats, 7 % -  in female rats. It determined that melatonin-positive-labeled cells in the gastric mucosa presents 3d cell types, which differ in size and structure. The number of different cell types different in males and females. Melatonin-positive-labeled cells in male rats were significantly lower than the melatonin-positive-labeled cells in female rats in both seasons. Key words: melatonin, melatonin-producing cells, stomach, pineal gland, seasons, sex.    ХАРАКТЕРИСТИКА КІЛЬКОСТІ МЕЛАТОНІН-ПОЗИТИВНО-МІЧЕНИХ КЛІТИН СЛИЗОВОЇ ОБОЛОНКИ ШЛУНКА У ЩУРІВ РІЗНОЇ СТАТІ У ОСІННЬО-ЗИМОВИЙ ПЕРІОД   В. В. Гнатюк   Національний фармацевтичний університет, Харків, Україна   Реферат Проведено дослідження кількості мелатонін-позитивно-мічених клітин слизової оболонки шлунка щурів різної статі віком 9 міс в осінньо-зимовий період. Встановлено, що в період сезонного фізіологічного десинхронозу -  восени - кількість мелатонін-позитивно-мічених клітин була меншою порівняно до їх рівня в зимовий період на 13% - у щурів-самців, на 7% - у щурів-самок. Визначено, що мелатонін-позитивно-мічені клітини  в слизовій оболонці шлунка представлені 3-а типами клітин відмінних за розміром на будовою. Кількість різних типів клітин відрізняється у щурів самців та самок. Загальна кількість мелатонін-позитивно-мічених клітин у щурів-самців достовірна нижча за їх кількість у щурів-самок в обидва сезони. Ключові слова: мелатонін, мелатонін-продукуючи клітини, шлунок, епіфіз, сезони, стать.   ХАРАКТЕРИСТИКА КОЛИЧЕСТВА МЕЛАТОНИН-ПОЛОЖИТЕЛЬНО-МЕЧЕНЫХ КЛЕТКОК СЛИЗИСТОЙ ОБОЛОЧКИ ЖЕЛУДКА У КРЫС РАЗНОГО ПОЛА В ОСЕННЕ-ЗИМНИЙ ПЕРИОД   В. В. Гнатюк   Национальный фармацевтический университет, Харьков, Украина   Реферат Проведено исследование количества мелатонин-положительно-меченых клеток слизистой оболочки желудка крыс разного пола в возрасте 9 мес в осенне-зимний период. Установлено, что в период сезонного физиологического десинхроноза - осень - количество мелатонин-положительно-меченых клеток меньше по сравнению с их уровнем в зимний период на 13% - у крыс-самцов, на 7% - у крыс-самок. Определено, что мелатонин-положительно-меченные клетки в слизистой оболочке желудка представлены 3-я типами клеток, которые отличаются размером и строением. Количество разных типов клеток отличается у самцов и самок.  Общее количество мелатонин-положительно-меченых клеток у крыс-самцов достоверно ниже их количества в сравнении с крысами-самками в оба сезона. Ключевые слова: мелатонин, мелатонин-продуцируюшие клетки, желудок, эпифиз, сезоны, стать.